EFEKTIVITAS PENGGUNAAN MANAJEMEN LEAN TERHADAP PENINGKATAN MUTU SISTEM PELAYANAN DI RUMAH SAKIT DI INDONESIA: STUDI LITERATUR - Faza Duta Pramudyawardani; Safinah Annajah; Siti Humaira Syarif; Novita Dwi Istanti (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
As a component whose benefits are expected, hospital management also focuses on the effectiveness of patient health services. By using appropriate management, problems related to patient complaints, waiting times, drug distribution to the performance of health workers can be measured. The management in question is by applying the concept of Lean. The use of the Lean concept in hospital management is proven to be able to reduce problems in patient care and even hospital organization. This also has an impact on improving the quality of the hospital concerned. This study aims to determine the effectiveness of using Lean management to improve the quality of service systems in hospitals in Indonesia. This research uses the method of literature study or Systematic Literature Review with national quality scientific journals as data. The results of the research show that the effectiveness of the use of Lean management applied in Indonesia is already going well. Hospitals benefit especially in the field of 5M (Man, Money, Material, Method, Machine) utilization.